Close and distant: Contrasting the metabolism of two closely related subspecies of Scots pine under the effects of folivory and summer drought. Issue 21 (25th September 2017) - Rivas‐Ubach, Albert; Sardans, Jordi; Hódar, José Antonio; Garcia‐Porta, Joan; Guenther, Alex; Paša‐Tolić, Ljiljana; Oravec, Michal; Urban, Otmar; Peñuelas, Josep
Abstract: Metabolomes, as chemical phenotypes of organisms, are likely not only shaped by the environment but also by common ancestry. If this is the case, we expect that closely related species of pines will tend to reach similar metabolomic solutions to the same environmental stressors. We examined the metabolomes of two sympatric subspecies of Pinus sylvestris in Sierra Nevada (southern Iberian Peninsula), in summer and winter and exposed to folivory by the pine processionary moth. The overall metabolomes differed between the subspecies but both tended to respond more similarly to folivory. The metabolomes of the subspecies were more dissimilar in summer than in winter, and iberica trees had higher concentrations of metabolites directly related to drought stress. Our results are consistent with the notion that certain plant metabolic responses associated with folivory have been phylogenetically conserved. The larger divergence between subspecies metabolomes in summer is likely due to the warmer and drier conditions that the northern iberica subspecies experience in Sierra Nevada. Our results provide crucial insights into how iberica populations would respond to the predicted conditions of climate change under an increased defoliation in the Mediterranean Basin. Abstract : This study provides new key knowledge on how two closely related subspecies (one authoctonous and one introduced) metabolically cope with the same environment conditions. We show how the introduced pine subspecies experience larger metabolome shifts in summer than the authoctonous one due to a more severe natural drought and warming conditions. Interestingly we also show how local metabolic responses to herbivore attack are more conserved throughout evolutionary history while systemic metabolic responses changed between subspecies.